Ag nanoparticles anchored on NiO octahedrons (Ag/NiO composite): An efficient catalyst for reduction of nitro substituted phenols and colouring dyes. (March 2022) - Bhatia, Pooja; Nath, Mala
Abstract: The development of an efficient sustainable catalyst for effective removal of hazardous chemicals, viz. nitrophenols and organic dyes, from wastewater is a challenging task. Herein, facile synthesis of Ag/NiO composites by anchoring Ag nanoparticles (NPs) on NiO octahedrons with different amounts of Ag NPs (AN-5% (5% Ag), AN-10% (10% Ag) and AN-15% (15% Ag)) has been demonstrated. SEM (scanning electron microscopic) and TEM (transmission electron spectroscopic) images ensured the proper anchoring of spherical Ag NPs (particle size = 16.54 ± 1.88 nm) on octahedron particles of NiO, which was also ensured by XPS (X-ray photoelectron spectroscopy) analysis. Moreover, the resulting composites have an average surface area (49–52 m 2 g ‒1 ) and pore size (2.39–2.26 nm). All three synthesized Ag/NiO composites (100 μL) catalyzed the complete reduction of para -np (4-nitrophenol: 0.1587 mM) within 2–3 min in the presence of 0.04 M NaBH4 . Among them, AN-5% has been chosen because of the lowest anchored Ag (5%) to obtain the optimized catalyst's amount (50 μL) and concentration of para -np (0.1587 mM). AN-5% also exhibited excellent catalytic activity towards different nitro substituted phenols, viz. ortho -np (2-nitrophenol), meta -np (3-nitrophenol), para -np (4-nitrophenol) and tri -np (2, 4, 6-trinitrophenol). AN-5% displayed ∼100% catalytic efficiency for reducing meta -np in 2 min with the apparent first order rate constant (kapp ) and normalized rate constant (Knor ) as 1.99 s −1 and 398.14 s −1 g −1, respectively. Additionally, AN-5% (29.41 μg mL −1 ) reduced >95% of the colouring dyes (10 ppm) such as CONG-R (congo red: 95% in 6 min), METH-O (methyl orange: 97.5% in 7 min), METH-B (methylene blue: 98.3% in 10 min) and RHOD-B (rhodamine B: 99.2% in 5 min). AN-5% not only demonstrated catalytic reduction towards individual pollutants, but also showed excellent activity for reduction of the mixtures of nitrophenols/dyes and for treatment of simulated industrial effluent samples (EFF1, EFF2) and a real industrial sample (textile dye-bath effluent). AN-5% can also be reused up to several cycles with almost same efficiency and followed the Langmuir-Hinshelwood apparent first order kinetics model. Graphical abstract: Ag nanoparticles in-situ anchored onto octahedron NiO uniformly. Ag/NiO composite efficiently reduced nitro substituted phenols and organic dyes in very less time. Image 1 Highlights: Different amounts of Ag NPs (5, 10 and 15%) anchored on the surface of octahedral NiO. The effect of concentrations of catalyst, para -np and NaBH4 on the catalytic reduction of para -np was observed. AN-5% composite efficiently reduce nitro substituted phenols and colouring dyes. AN-5% shows good reusability for reduction of para -np and CONG-R.